Curcumin effect on Bleomycin-induced pulmonary fibrosis in Mus musculus - Rahmi, Annisa; Setiyono, A.; Juniantito, V. (Indonesian Animal Sciences Society, 2015)
Curcumin, a curcuminoid compound of turmeric has been demonstrated to have anti-oxidant and anti-inflammatory properties. Bleomycin (BLM) is an anti-cancer drug induced pulmonary fibrosis in human and animals. This study was aimed to investigate biological effects of curcumin on bleomycin-induced pulmonary fibrosis in mice (Mus musculus) through pathomorphological assessment. In this study, 16 mice ddy strain were divided into four groups, namely (i) control, mice were subcutaneously (SC) injected with 100 Âµl sterilized aquadest in dorsal skin, (ii) BLM group, injected SC with 100 Âµl of 1 mg/ml BLM in dorsal skin, (iii) Curcumin (CMN) group, mice were intraperitoneally (IP) injected with 100 mg/kg body weight (BW) curcumin dissolved in 0,5% carboxy methyl cellulose (CMC) and injected with 100 Âµl sterilized aquadest SC, (iv) BLM+CMN group, injected SC with 100 Âµl of BLM 1 mg/ml and injected IP with 100 mg/kg BW CMN in 0,5% CMC. All treatments were performed daily for four weeks period. The lung samples were collected and fixed in buffered neutral formalin (BNF) 10%. Histopathological evaluation was performed with hematoxylin-eosin (HE) and Massonâs trichrome (MT) stains. The results showed that BLM treatment significantly increased fibrosis area and alveolar wall area fraction as compared to control. OIn the other hand, CMN treatment significantly reduced fibrosis area and alveolar wall area fraction in mice treated with BLM. In conclusion, our study showed that CMN treatment may inhibit lung fibrogenesis in BLM-induced pulmonary fibrosis. Key Words: Bleomycin, Curcumin, Mice, Pulmonary Fibrosis